The Relationship between Spiritual Health and Public Health Aspects among Patients with Breast Cancer - Mohammad Moradi-Joo; Towhid Babazadeh; Zeynab Honarvar; Sahar Mohabat-Bahar; Fatemeh Rahmati-Najarkolaei; Morteza Haghighi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Spiritual well-being is one of the fundamental concepts in chronic diseases and is considered an important approach to improve public health among individuals. Given the importance of spiritual well-being and its role in the promotion of mental health, the present study was conducted with the aim of evaluating spiritual well-being and mental health in patients with breast cancer who visited a center for cancer control at the University of Medical Sciences. Method: This cross-sectional study was conducted on 122 patients with breast cancer in 2015. The data were collected through self-administered 20-item Paloutzian & Ellison's Spiritual Well-Being Scale and a 28-item questionnaire of mental health after determining their validity and reliability. The collected data were then analyzed using ANOVA and Pearson correlation and linear regression. Results: The results show that most patients had moderate spiritual health (37.8%), and most of them suffered mild mental health problems. (50 percent). Furthermore, there was a significant relationship between mental health and demographic characteristics (Marital status, education, income, physical activity). There was also a significant relationship between mental health and spiritual health. Conclusion: According to the findings, to prevent mental suffering among patients with breast cancer, promoting spiritual health of patients should be regarded as one of the priorities of health care professionals. For downloading the full-text of this article please click here.